New Insights into Antibacterial Compounds: From Synthesis and Discovery to Molecular Mechanisms of Action - Jorge H. Leitão (MDPI AG, 2020)
The worldwide emergence of microbial resistance to available antibiotics presents a global threat to public health and health systems. This special issue aimed to gather papers describing novel antibiotics, originating form chemical synthesis, repurposing of existent drugs, or from natural sources like plant extracts, herbs and spices. A total of 13 papers were published, covering a wide range of topic, including antimicrobial resistance surveillance studies; synthesis of novel molecules with antimicrobial activities; modification or repurposing of already existing molecules, plant-derived active extracts, and molecules; the effects of antimicrobial therapy on microbiota; and the investigation of novel formulations for human and veterinary uses. After decades of antibiotics discovery decline, antibiotics discovery is boosting. Recent developments of post genomics approaches and bioinformatics tools will most certainly turn the tide in the discovery and development of antimicrobials in this exciting field.